Acquisition of anti-phosphatidylserine IgM and IgG antibodies by infants and their mothers over time in Uganda - Tijani, Muyideen Kolapo; Saleh, Bandar Hassan; Lugaajju, Allan; Danielsson, Lena; Persson, Kristina E. M. (Frontiers in Immunology, 2024)
Background: Production of anti-phosphatidylserine (anti-PS) antibodies has been associated with malaria and can aggravate pathology. How these autoantibodies develop during early childhood in a malaria context is not known. We examined levels of anti-PS IgG and IgM antibodies in a longitudinal cohort of mother-baby pairs during birth, in the infants at 2.5, 6 months, and in mothers and their babies at 9 months postpartum. Results: There was no difference between levels of anti-PS IgG in cord blood and the mothers' peripheral blood at birth. However, anti-PS IgM levels were significantly higher in the mothers compared to the infants' cord blood, and IgM levels were steadily increasing during the first 9 months of the infants' life. In infants that had the highest anti-PS IgM levels at birth, there was a decline until 6 months with a rise at 9 months. Infants that possessed high anti-PS IgG at birth also exhibited a progressive decline in levels. When anti-PS were correlated to different fractions of B-cells, there were several correlations with P. falciparum specific atypical B cells both at birth and at 2.5 months for the infants, especially for anti-PS IgM. Anti-PS also correlated strongly to C1q-fixing antibodies at birth. Conclusion: These results show that anti-PS IgG acquired by mothers could be transferred transplacentally and that IgM antibodies targeting PS are acquired during the first year of life. These results have increased the knowledge about autoimmune responses associated with infections in early life and is critical for a comprehensive understanding of malaria vaccine functionality in endemic areas.